Medicinal Plants Recorded from Pine Forest of Hills East Khasi District, Meghalaya - Hynniewta, Sierra Rebecca; Pinokiyo, Athokpam; Suchitra Devi, H.; Elangbam, Meena (Indian Forester, 2019)
A total of 27 plant species have been collected and identified with their local names and local medicinal uses from Pine forests of East Khasi hills district, Meghalaya. These are represented by 16 families viz., Asteraceae with 7 spp., Rosaceae with 3 spp., Rubiaceae with 3 spp., Lamiaceae with 2 spp. and Anacardiaceae, Apiaceae, Commmelinaceae, Cyperaceae, Caryophyllaceae, Euphorbiaceae, Malvaceae, Melastomataceae, Smilacaceae, Plantaginaceae, Polygonaceae, Verbenaceae with 1 sp. each. These plants could be used for introduction in new pine forest plantations.